Factors Associated With Quality of Life of Family Caregivers of Dialysis Recipients. (March 2020) - Starks, Shaquita A.; Graff, J. Carolyn; Wicks, Mona N.
Chronic kidney failure may contribute to the diminished quality of life of African American women who care for adults affected by the disorder. Few studies document the quality of life of these caregivers. For this descriptive correlational study, caregiver demographic, caregiver burden, depressive symptoms, family functioning, and quality-of-life self-report data from 75 African American women were extracted from an existing database. Ferrans' Conceptual Model of Quality of Life guided the selection of study variables. Several significant associations were found. Caregiver education, employment status, marital status, and caregiver burden explained 63% of the variance in the caregivers' quality of life. Findings support the need to explore further and design interventions to improve the quality of life of working African American women supporting individuals with chronic kidney failure.